The effect of quantitative traits on grain productivity of maize hybrids depending on climatic conditions - G. Ya. Krivosheev; A. S. Ignatiev (Зерновое хозяйство России, 2024)
The purpose of the study was to identify the effect of quantitative traits on grain productivity of maize hybrids depending on moisture availability.   The study was carried out on the breeding field of the laboratory for maize breeding and seed production of the FSBSI “ARC “Donskoy” in 2020–2023. The soil of the experimental plot was ordinary blackearth, with a humus layer thickness of 140 cm. The climate is characterized by aridity with unstable moisture. The years of the study were contrasting in temperature and moisture availability (HTC 0.49–0.83). Due to the uneven distribution of precipitation during a vegetation period of maize, the temperature regime through the months and moisture availability had even greater differences (HTC 0.11–2.28). The objects of research were 96 maize hybrids. The main method for developing hybrids was an interline hybridization. There has been identified a stable correlation between grain productivity and quantitative traits in each of the four years of study, when ‘one ear weight’ was r = 0.34±0.09 – 0.64±0.08 and ‘number of grains in a ear row’ was r = 0.35±0.09–0.58±0.08. The specific climatic conditions of some years of the study (one year out of four) influenced the lack of correlation between amount of productivity and quantitative traits with ‘number of ears per plant’ (r = 0.11 ± 0.10 in 2022), ‘number of grains per ear’ (r = 0.01±0.10 in 2023), ‘grain yield during threshing (r = 0.04±0.10 in 2023). The correlation between productivity and traits was subject to even greater variability depending on weather conditions with ‘ear attachment height’ (r = 0.01±0.10–0.40±0.09), ‘plant height’ (r = 0.16±0.10–0.38±0.09), ‘ear diameter’ (r = -0.02±0.10–0.43±0.09), ‘1000-grain weight’ (r = -0.14±0.10–0.45±0.09). In all years of the study, there were no correlation between productivity and such traits as ‘number of grain rows’ (r = -0.27±0.09–0.17±0.10) and ‘ear length’ (r = 0.01±0.10–0.29±0.09).